2017
DOI: 10.18203/2394-6040.ijcmph20175357
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and QOL among rural elderly

Abstract: Background: Aging is a natural phenomenon and quality of life among elderly gets compromised. The biggest killers among old age are heart disease and stroke and greatest cause of morbidity are sensory abilities, Diabetes and depression. The life of elderly gets compromised when they start facing problems to fulfil basic requirements such as social relations; personal care, nutrition and accommodation added to old age health problems.Methods: It was a community based cross sectional study from June to September… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Our study has similar resemblance with the study reported by Satyanarayana PT et al . [ 17 ] in Hoskote (2017) and Bhandari N et al . [ 14 ] in Nepal (2016) ( P value < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Our study has similar resemblance with the study reported by Satyanarayana PT et al . [ 17 ] in Hoskote (2017) and Bhandari N et al . [ 14 ] in Nepal (2016) ( P value < 0.001).…”
Section: Discussionmentioning
confidence: 99%